CONTRIBUTION OF THE WORK INTEGRATED LEARNING (WIL) LEARNING PROGRAM TO THE FINAL RESULTS OF INDUSTRIAL WORK PRACTICE AT TARAKANITA SCHOOL OF COMMUNICATION AND SECRETARIAL STUDIES - Yakin Bakhtiar Siregar; Linda Lin- Chin Lin (Jurnal Administrasi dan Kesekretarisan, 2024)
The Work Integrated Learning (WIL) learning program is a prerequisite course to equip students before joining the apprenticeship program. The problem in this study is whether the WIL score has a contribution to the final apprenticeship score. This study aims to describe and analyze how big the relationship and influence of WIL course grades on the apprenticeship grade. Quantitative research method using secondary data. The research population was 167 students with a sample of 118. The data collection technique in this study was through documentation, namely in the form of final grades for WIL courses and final results of apprenticeship. The data analysis technique used descriptive analysis and simple linear regression. The average score for WIL is 81.83 and the final apprenticeship score is 84.70. The results showed that the WIL value had a significant effect on the final score. The WIL value variable contributed 11,6% to the final apprenticeship score. The WIL score has a moderate correlation with the final apprenticeship score.